Economic integration and FDI: an empirical analysis of foreign investment in the EU and in Central and Eastern Europe - Brenton, Paul,DiMauro, Francesca,Lücke, Matthias (ACE Programme Management, 2001)
Recent evidence suggests that regional economic integration provides an important stimulus not only to trade, but also to FDI. In contrast, the available theory on FDI does not yet provide empirically testable propositions on the effects of concurrent trade and investment liberalisation. Moreover, given the limits of simulation models, which rely heavily upon parameter choice, in assessing the impact of such liberalisation, there is a need for empirical analysis to identify the principal features of FDI. This paper uses a
Keywords: Graue Literatur; Auslandsinvestition; Gravitationsmodell; EU-Mitgliedschaft; Internationale Wirtschaftsbeziehungen; Wirtschaftsintegration; Schätzung; EU-Staaten; Osteuropa; Foreign Direct Investment; Transition Economies; Gravity Model